Penerapan Mesin Pencacah Kertas untuk Meningkatkan Produktivitas Daur Ulang dan Mengurangi Dampak Perubahan Iklim Akibat Pembakaran Sampah - Yunus, Yunus; Arizal, Heru; Prakoso, Albrian Fiky; Ramis, Irfan; Abdillah, Moh Bima Fahrosyid Rizki (Universitas Nusantara PGRI Kediri, 2025)
This service aims to overcome the problem of paper waste management to destroy unnecessary archives at the partner, namely the Directorate of Law and Administration of Surabaya State University. At the partner, the destruction process is carried out by shredding using scissors and tearing it into pieces. This method is ineffective and inefficient because it requires a lot of energy and a long time. In fact, in forced conditions, burning is carried out. This creates new problems, namely in the long term it will encourage climate change and environmental pollution. The solution to solving this problem is to process paper waste using a waste shredding machine to increase the recycling process and reduce the impact of climate change due to waste burning. The implementation method includes socialization of PKM-LK to partners, activity planning stage, manufacturing stage, paper shredding machine function test stage, training and mentoring stage, TTG (Appropriate Technology) implementation stage, and monitoring and evaluation stage. The results of the activity show that using a waste paper shredder machine is effective, efficient, and can reduce climate pollution due to waste burning with the number of sheets of paper processed per hour ± 2570 sheets, and the total weight of paper processed ± 12.83 kg. The recommendation from this study is to expand the market, machines can be designed with varying capacities, from small scale for SMEs to large scale for companies.